Introduction to 2020-2 - Buch, Anders (Nordic Journal of Working Life Studies, 2020)
This issue of Nordic Journal of Working Life Studies compiles five articles that introduce different themes and concerns in contemporary Nordic working life. Rolle Alho’s article ‘You Need to Know Someone Who Knows Someone’: International Student’s Job Search Experiences explores the job search strategies and obstacles that international students meet when they seek to enter the job market in Finland. Through 31 qualitative interviews with international students from Finnish universities, he investigates how the students are embedded in the Finnish community and how they make use of their knowledge and connections to obtain a job in Finland. Both formal and informal strategies are often employed, but the international students are clearly disadvantaged in lacking novel information about job opportunities that are only chan- neled through informal sources. Sectorial differences are significant for the successfulness of the job search; sectors with a shortage of labor leaves better opportunities for international students to enter the job market (...)